Pembimbingan dan Pendampingan Pendaftaran HKI Merek Dagang pada UMKM di Desa Kualu Kabupaten Kampar - Fira Nabilah Ardi; Anisa Mutamima; Tiara Indah Fitrianingrum (Warta Pengabdian Andalas, 2022)
Mutiara Ayu is a Micro, Small, and Medium Enterprise (MSME) founded in November 2020 by a group of housewives in Mutiara Kualu 8 Housing Complex, Kualu Village, Tambang District, Kampar Regency. Mutiara Ayu produces Healthy Soybean Milk using natural ingredients without the addition of preservatives, artificial sweeteners, and synthetic flavors. In running their business, MSME Mutiara Ayu experienced various problems, such as the production process was not optimal, the product was not standardized and certified, and the trademark was not registered. The University of Riau Abdimas team was integrated with the Real Work Lecture (Kukerta) program in partnership with MSME Mutiara Ayu by assisting in solving the problems being faced by increased knowledge and skills. One of the activities carried out was guidance and assistance in registering trademarks. Through this activity, it was hoped that Mutiara Ayu could understand the procedures and register their trademarks at the Ministry of Law and Human Rights (Kemenkumham). With the official registration of trademarks at the Ministry of Law and Human Rights, Mutiara Ayu could obtain the power and legal protection for registered trademarks, could promote and market products in the broader market, increase competitiveness in the business, and prevent products from plagiarism.